História de vida em pesquisas qualitativas o caso de Beatriz - Alves, Ana Paula Ribeiro (Editora Oficina Universitária, 2022)
In this book, the reader will learn step by step how to use the Life Story method in qualitative research. In a clear and objective way, the authors expose practical examples of each instrument that composes the method and beyond, the analysis that best corresponds to this type of collection and the final format of the edited text in thesis, dissertation or others. Taking into account the doubts that arise when collecting, analyzing and writing the life history and noting the scarce literature in the area, this is a guide that brings together all the steps and mishaps that the future researcher may encounter in the process.